Public health preparedness at the community level - Smith, Vickie (My University, 2014)
Although public health departments were introduced to the threat of bio-warfare during the events of the Cold War in the 1950’s and 60’s, it was the terrorist events of September 11, 2001 and subsequent anthrax scares that prompted the federal government to increase support of preparedness initiatives at the state and local levels. Despite extensive improvements in public health infrastructure including initiatives for laboratory surveillance, risk communication, and preparedness training, significant gaps remain in local health department preparedness programs. Twelve years after 9/11 there are still significant challenges in funding, staffing, leadership, and workforce development. Continued improvements in coordination between public health, emergency responders and the private sector are essential to reducing the capability gaps in emergency response.
Keywords: Public health; Emergency; Preparedness; Public Health (0573)